Training report on integration of gender equality and social inclusion considerations in the accelerated innovation dissemination initiative in the Great Lakes region - rapid delivery hubs (AID-I GLR) for scaling partners in the Democratic Republic of Congo - Liani, M.; Kasonia, L.; Nyangezi, A.A.; Mulumeoderhwa, S.; Amato, M.; Nabahungu, L.; Konlambigue, Matieyedou; Mignouna, J. (International Institute of Tropical Agriculture, 2024)
A two-day training course on Gender Equality and Social Inclusion (GESI) Considerations in the Great Lakes Accelerated Innovation Delivery Initiative Delivery Hub (AID-I GLR) project was held from 2nd to 3rd October 2023 at IITA's Kalambo Research Station in South Kivu Province, Democratic Republic of Congo (DRC). The training was organized by IITA AID-I GLR team under guidance of Dr. Millicent Liani (IITA), the project’s GESI technical lead, with the support of Mrs Lydie KASONIA (GESI focal person for DRC, and in charge of environmental and social protection at Rikolto). Participants came from six territories in South Kivu - where the AID-I GLR Project is being implemented. They included agricultural extension officers, members of cooperatives, extension agents, agricultural engineers, agronomist, veterinarians and monitoring and evaluation and Learning (MEL) officers (see list of participants in Annex 1). The objectives of the training were to provide participants with: (1) knowledge of the basic concepts of gender research and how they relate to agricultural research work and in particular to the dissemination of agricultural innovations; (2) an understanding of where gender work is integrated into the AID-I GLR project and embrace gender and social inclusivity in scaling of innovations and technologies; (3) ability to integrate GESI lens and various approaches throughout the project cycle; and (4) the potential to become gender champions for the AID-I GLR project and other related initiatives. The facilitators used various approaches to stimulate discussion among the participants, including the use of role-plays, group discussions and plenaries, as well as the use of assorted cards, which made the training both lively and productive. The facilitators felt that the training was timely in providing a better understanding of GESI and its role in the AID-I GLR project and in agricultural research in general, as most participants were initially sceptical about gender issues due to the responses about aversion to gender research as highlighted on the cards. However, as the training progressed, they began to understand and appreciate the importance of GESI integration in scaling of agricultural innovations. Participants were engaged in the learning process, as evidenced by the group discussions and plenary presentations, as well as during recaps including the conversations that continued throughout the training sessions. However, the training had its limitations as the two-day training was not enough to engage participants in such difficult and deep discussions, as most of them had never received training on GESI before. Therefore, the number of days needed to organize future training workshops should depend on the information and materials we prepare and provide in subsequent training sessions. Pre-and post-training tests showed a great improvement in the understanding of GESI issues.